2021
DOI: 10.3390/w14010053
|View full text |Cite
|
Sign up to set email alerts
|

Water Use Characteristics of Two Dominant Species in the Mega-Dunes of the Badain Jaran Desert

Abstract: The sparse natural vegetation develops special water use characteristics to adapt to inhospitable desert areas. The water use characteristics of such plants in desert areas are not yet completely understood. In this study, we compare the differences in water use characteristics between two dominant species of the Badain Jaran Desert mega-dunes—Zygophyllum xanthoxylum and Artemisia ordosica—by investigating δ2H and δ18O in plant xylem (the organization that transports water and inorganic salts in plant stems) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Despite the harsh conditions, desert ecosystems often comprise multizonal vegetation, and species that have typical characteristic of adaptation to drought, which is the main property determining desert productivity [ 9 , 27 ]. Among these species, Artemisia ordosica is one of the most dominant subshrubs and is distributed widely in the sandy areas of northwest China, such as Inner Mongolia, Ningxia, Shaanxi, Gansu, and other provinces [ 28 , 29 , 30 ]. Artemisia ordosica can adapt well to water stress conditions and has developed the typical morphological and physiological characteristics of adaptation to drought and sand burial [ 29 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the harsh conditions, desert ecosystems often comprise multizonal vegetation, and species that have typical characteristic of adaptation to drought, which is the main property determining desert productivity [ 9 , 27 ]. Among these species, Artemisia ordosica is one of the most dominant subshrubs and is distributed widely in the sandy areas of northwest China, such as Inner Mongolia, Ningxia, Shaanxi, Gansu, and other provinces [ 28 , 29 , 30 ]. Artemisia ordosica can adapt well to water stress conditions and has developed the typical morphological and physiological characteristics of adaptation to drought and sand burial [ 29 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, deep soil water absorbed by the roots of Z. xanthoxylum is released into the upper soil layers, wherein it can be utilized by the shallow branching roots of F. bungeana . In addition, Artemisia ordosica , which grows in the same dune habitat, utilizes soil water at depths down to 120 cm ( Qin et al., 2022 ), thereby to a certain extent, drawing upon the water sources of F. bungeana . Consequently, there may exist a certain degree of competition between F. bungeana and A. ordosica for limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, deeper soil is influenced to a far lesser extent by environmental factors, and consequently, the levels of soil moisture in these deeper layers tend to be higher and less prone to fluctuate than those in shallower soils ( Wang et al., 2017 ). From the perspective of the water potential gradient, we determined that water in the wet sand layers of mega-dunes is derived from groundwater, which migrates upward by evaporation as a thin film of water ( Chen et al., 2004 ; Chen et al., 2014 ), thereby leading to a greater isotopic enrichment of the surface soil water ( Qin et al., 2022 ). This process tends to run counter to the idea that local precipitation can infiltrate through mega-dunes to recharge lakes or groundwater ( Zhao et al., 2011 ; Ma et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of dominant natural species' response to soil water dynamics in extreme dry shifting desert regions, Qin et al [7] compared the differences in the water use characteristics between two dominant species of the Badain Jaran Desert mega-dunes-Zygophyllum xanthoxylum and Artemisia ordosica-by investigating 2 H and 18 O in plant xylem and soil water and 13 C in plant leaves. The results confirmed that the differences in water use between the two studied species were mainly related to their root distribution characteristics.…”
Section: Summary Of the Special Issuementioning
confidence: 99%